The Effect of Tracheal Stenosis on Airflow in the Trachea and Main Bronchi:A Numerical Modelling Analysis - Nasrul Hadi, Johari; Kahar, Osman; Mohammed Rafiq, A. Kader (Publishing Technology, 2013)
The location and size of tracheal stenosis are among the major factors that contribute significantly to the breathing difficulties. Hence, this study aims to establish correlation between the location and size of the stenosis to the possibility of breathing difficulties. This work used ideal trachea model based on realistic trachea model derived from Computed Tomography (CT) scan images. The stenosis was patched to the healthy trachea models at regular locations and sizes as proposed by medical practitioners. The changes in the flow behavior due to the different sizes and locations of the stenosis were then examined to determine the pattern of possible breathing difficulties. The present simulation confirms that the overall flow behavior could be significantly affected if the size of stenosis is more than 60% for location far from the bifurcation region, and at size of 50% for location close to the bifurcation region. The outcomes of this study may help the medical practitioners and researchers to understand how dramatic increase in pressure drops occurs inside the trachea and main bronchi with the presence of stenosis at different location and size.